2016
DOI: 10.1111/aos.12960
|View full text |Cite
|
Sign up to set email alerts
|

Donor sclera‐wrapped acrylic orbital implants following enucleation: experience in 179 patients in the Netherlands

Abstract: ABSTRACT.Purpose: To report the postoperative results after enucleation of using an acrylic orbital implant covered in donor sclera for implantation. Methods: We retrospectively analysed the charts of patients who were enucleated between 2007 and 2011. Only patients who received an acrylic implant covered with donor sclera were included. Results: A total of 179 patients were included in our analysis. About 15.6% experienced postoperative problems of which the majority were related to the position of the eyelid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…In the human literature, reported complications include implant displacement (20%), sulcus deformity (12%–18%), implant extrusion (0.6%–10.6%), eyelid laxity (5.3%), conjunctival granuloma (5.3%), hemorrhage (10%), cellulitis (0.6%), infection (0.56%–0.7%), cyst formation (1.3%–1.6%), dehiscence (2.6%–2.9%), conjunctival contracture (5.4%), and ptosis (20.9%) 8–22 . In comparison, the authors of the present study found higher rates of cellulitis, infection, implant migration, and implant extrusion.…”
Section: Discussionmentioning
confidence: 99%
“…In the human literature, reported complications include implant displacement (20%), sulcus deformity (12%–18%), implant extrusion (0.6%–10.6%), eyelid laxity (5.3%), conjunctival granuloma (5.3%), hemorrhage (10%), cellulitis (0.6%), infection (0.56%–0.7%), cyst formation (1.3%–1.6%), dehiscence (2.6%–2.9%), conjunctival contracture (5.4%), and ptosis (20.9%) 8–22 . In comparison, the authors of the present study found higher rates of cellulitis, infection, implant migration, and implant extrusion.…”
Section: Discussionmentioning
confidence: 99%
“…1. Метод оперативного вмешательства: энуклеация; эвисцерация с резекцией роговицы, Для уменьшения риска послеоперационных осложнений, особенно при энуклеации, важно выбрать оптимальный материал имплантата [8]. У 121 пациента (91,7 %) был использован орбитальный вкладыш из пористого ПТФЭ, характеризующийся биосовместимостью, легкостью стерилизации, возможностью ручной обработки, низким риском инфицирования, миграции и экструзии, приемлемой стоимостью [9][10][11].…”
Section: материалы и методыunclassified
“…Jongman et al 18 (level III) reviewed 179 patients (mean age, 60.9 years) for an average of 12.6 months after enucleation with placement of a sclera-wrapped acrylic implant. Three patients experienced complications: 1 demonstrated implant exposure, 1 demonstrated orbital cellulitis, and 1 experienced intractable chemosis (0.6% for each complication).…”
Section: Adult Populationmentioning
confidence: 99%